Heart transplantation from cardiac arrest-resuscitated donors - V. N. Poptsov; E. A. Spirina; V. V. Pchelnikov; V. M. Khatutsky; E. Z. Aliev; V. Yu. Voronkov; L. R. Nazipova; A. S. Yepremyan; E. N. Zolotova; A. I. Skokova; P. M. Aghasyan (Вестник трансплантологии и искусственных органов)
Heart transplantation from сardюpulmonary resuscitated (CPR) donors is one of the way to increase the availability of heart transplantation (HT). The study included 28 recipients: 25 (89,3%) men and 3 (10,7%) women at the age 20-68 (46,2 ± 13,7) who underwent HT from CPR donors in the V.I. Shumakov National Medical Research Center of Transplantology and Artificial Organs in the period from 01.01.2011 to 31.12.2017, that was 4.0% of the total number of HT (n = 698). CPR donor group and control group had no significantly differences in early cardiac transplant dysfunction and 1-, 3- and 5-year survival.